Legal Consequences of Notary Deeds Through the Validity of Electronic Signatures - Larasati , Dyah Wening; Aditya, Abdul Kholik; Aprilia , Putri; Sutrisno , Endang; Umar , Jaenudin (PT FORMOSA CENDEKIA GLOBAL, 2025)
The advancement of contemporary society has ushered in an era of technological disruption, leading to a transformation in the understanding of many concepts, including legal principles. Electronic signatures, which serve as a substitute for manual signatures, are a product of contemporary technological advancements. A notary is a public official empowered to create legitimate documents, including the establishment of legal entities and other official acts under laws and regulations. This study aims to investigate the legal implications of notaries using electronic signatures for creating business documents in the context of PT or CV. The method used in this study is a normative juridical approach with a legislative focus and a literature review. The study results show that electronic or digital signatures can be used remotely to prepare GMS minutes signed by shareholders in public PTs. Juridically, using electronic signatures in notary deeds has consequences for the notary's legitimacy, power of proof, and responsibility. Legal harmonization between the UUJN and the ITE Law is necessary, as well as strengthening regulations to ensure that electronic signatures can be applied legally and safely in notarial deeds.